Labor Market Dynamics with Sorting - Bastian Schulz (Institute of Labor Economics (IZA), 2023)
I study a dynamic search-matching model with two-sided heterogeneity, a production complementarity that induces labor market sorting, and aggregate shocks. In response to a positive productivity shock, incentives to sort increase disproportionately. Firms respond by posting additional vacancies, and the strength of the response is increasing in firm productivity. The distribution of unemployment worker types adjusts slowly, which amplifies job creation in the short run. In the long run, falling unemployment curtails the firms' vacancy posting. The model closely matches time-series moments from U.S. labor market data and produces realistic degrees of wage dispersion and labor market sorting.
Keywords: E24; E32; J63; J64; 330; search; matching; sorting; mismatch; aggregate shocks; worker heterogeneity; firm heterogeneity; unemployment dynamics